BARRIERS PERCEIVED BY MANAGERS AND TEACHERS TO THE DEVELOPMENT OF SCIENTIFIC RESEARCH IN A PARAGUAYAN UNIVERSITY. - Díaz Gamarra, Marisa (2024)
SUMMARY Research is essential since it allows the development and evaluation of disciplinary knowledge, which has constituted a science. It is an unavoidable function for its professionals, however, it is little valued by institutions and little demanded in the actions of the profession. The objective of the research was to describe the barriers perceived by managers and teachers for the development of scientific research at the National University of Caaguazú. A study with a qualitative phenomenological, humanistic, naturalistic or ethnographic approach was carried out, it was framed in the phenomenological paradigm, it was carried out between the months of February and March 2023 in the different Academic Units of the National University of Caaguazú, 7 research directors and 12 teachers, including teachers, were taken into account. researchers and teachers of technical and/or practical areas. The barriers identified by directors to the advancement of scientific research in their academic unit are diverse. However, there are factors that favor research development in the faculties of the National University of Caaguazú. Among them, the requirements of evaluation agencies to carry out research, incentives through participation in conferences, presentation and awarding of works, and an institutional policy that grants credits to research teachers stand out. In addition, the commitment of staff, the existence of a scientific journal and a network of researchers, the proactive attitude of students and the promotion of research teachers contribute significantly, as does the desire to contribute to social well-being. Keywords: research, influence on research, gap, directives, docents,